Evaluation of the idiopathic scoliosis of varying severity treatment effectiveness with transpedicular systems - Yu. L. Zeynalov (Инновационная медицина Кубани)
Introduction Significant success has been achieved in the development of new methods of treatment and rehabilitation of patients with idiopathic scoliosis, however, in many aspects of this problem there is no unambiguous approach to the choice of a correction method, assessment of treatment results.Objective To study the results of treatment of patients with idiopathic scoliosis according to X-ray and MSCT data, as well as according to the questionnaire – the SRS-30, depending on the degrees of the deformity, the type of scoliosis.Material and methods The study is retrospective, single center. Evidence level – IV. In 300 patients with idiopathic scoliosis of varying severity at the age from 10 to 50 years, the immediate and long-term results of elimination of spinal deformity by the method of internal transpedicular fixation were studied. In the study we used polypositional radiography, multislice computed tomography (MSCT) and questionnaire SRS-30.Results In patients with spinal deformity up to 60 ° a year after surgery, no loss of correction was found. After elimination of the deformity at 60–90 °, loss of correction up to 2 ° was observed in 3.6% of patients. In patients with deformity greater than 90 °, the average postoperative progression of scoliotic deformity was 3.5 ± 0.7 °. When examining patients after 2–5 years, there was no loss of correction in the group with initial spinal deformity up to 60 ° and in the group from 60–90 °. In patients with deformity greater than 90 °, the postoperative progression of scoliotic deformity in persons over 25 years old was 4.5 ± 0.6 °, which is associated with degenerative changes in the spine.Conclusion The study of immediate and long-term results showed that 1 year after treatment, 94% of patients rated the treatment result as excellent and good, in 6% – as satisfactory. All patients noted a positive effect of the cosmetic and functional results of treatment, while 56% believed that they looked “better” than before surgery (4 points), 44% rated the effect at 5 points and noted that they looked “much better”. Long-term results were studied in 50 patients 10 years after surgery.